Creep lifetime prediction of virgin and service-exposed Super304H austenitic stainless steel boiler tubes based on hierarchical multiscale analysis and creep cavitation model. (2nd January 2020) - Pham, Li Qui; Nguyen, Vinh Phu; Jeong, Tae Min; Yoon, Kee Bong; Xu, Liming; Shin, Keesam; Choi, Seung Tae
ABSTRACT: Creep deformation of Super304H austenitic stainless steel boiler tubes in thermal power plants is evaluated using crystal elasto-viscoplastic finite element analysis (CEV-FEA). The material properties of Super304H at elevated temperatures are obtained from experiments and computations at different scales as follows: anisotropic elastic constants of Super304H at elevated temperatures (500–700°C) are obtained from molecular dynamics simulations; microstructures of virgin and service-exposed Super304H boiler tubes are observed using scanning electron microscopy; and macroscopic stress–strain and creep strain curves at 650°C are measured from tensile and miniature creep tests, respectively. Stress concentration evolution at a triple junction of grains featuring various combinations of crystallographic orientations in polycrystalline Super304H is evaluated using CEV-FEA during creep deformation. The remaining creep lifetime of polycrystalline Super304H austenitic stainless steel boiler tubes is estimated from the creep cavitation model, where the stress concentration at the triple junction is used as a representative stress driving creep cavitation. GRAPHICAL ABSTRACT: